2012
DOI: 10.1103/physrevb.86.104436
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the magnetic properties of Fe, Co, and Ni clusters and monolayers on Ir(111), Pt(111), and Au(111)

Abstract: We present a detailed theoretical investigation on the magnetic properties of small single-layered Fe, Co and Ni clusters deposited on Ir(111), Pt(111) and Au(111). For this a fully relativistic abinitio scheme based on density functional theory has been used. We analyse the element, size and geometry specific variations of the atomic magnetic moments and their mutual exchange interactions as well as the magnetic anisotropy energy in these systems. Our results show that the atomic spin magnetic moments in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
52
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 42 publications
12
52
0
7
Order By: Relevance
“…III D. hibits the same trend as µ spin for 3d atoms [45,46]. The explanation rests on the large SOC at Pt atoms in comparison with the SOC at Fe atoms: µ orb at Fe atoms is suppressed by the off-site SOC at Pt atoms.…”
Section: A Density Of Statesmentioning
confidence: 65%
“…III D. hibits the same trend as µ spin for 3d atoms [45,46]. The explanation rests on the large SOC at Pt atoms in comparison with the SOC at Fe atoms: µ orb at Fe atoms is suppressed by the off-site SOC at Pt atoms.…”
Section: A Density Of Statesmentioning
confidence: 65%
“…On the other hand, an increase in binding energy with cluster size is also reported in DFT studies (Stevanovic et al 2012). A DFT study involving Fe clusters supported on Ir (111) layers (Bornemann et al 2012) have shown that atomic magnetic moments are induced in the Ir substrate due to the presence of Fe atoms. Experimentally, Ir 4 clusters showing a tetrahedral geometry are synthesized on substrates (Deutsch et al 1997).…”
Section: Introductionmentioning
confidence: 86%
“…It has been known for some time that one such key factor is the coordination number, with smaller coordination numbers generally implying larger magnetic moments. [1][2][3] However, coordination numbers alone do not fully determine magnetism of nanostructures. The chemical composition can play a significant role as well.…”
Section: Introductionmentioning
confidence: 99%
“…An Fe monolayer, for instance, has a larger spin magnetic moment when deposited on Au(111) than when deposited on Pt(111), whereas for a Co monolayer it is vice versa. 3 The situation is even more diverse for the MAE where different substrates may lead to different properties of systems of otherwise identical geometries. For example, Co 2 and Ni 2 dimers on Pt(111) have out-of-plane magnetic easy axis but the same dimers on Au(111) have an in-plane magnetic easy axis.…”
Section: Introductionmentioning
confidence: 99%